2018
DOI: 10.1075/lab.17019.lag
|View full text |Cite
|
Sign up to set email alerts
|

Straight from the horse’s mouth

Abstract: We investigated the comprehension of subject-verb agreement in Turkish-German bilinguals using two tasks. The first task elicited speeded judgments to verb number violations in sentences that contained plural genitive modifiers. We addressed whether these modifiers elicited attraction errors, which have supported the use of a memory retrieval mechanism in monolingual comprehension studies. The second task examined the comprehension of a language-specific constraint of Turkish against plural-marked verbs with o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…2 For Group 3, it was run on a web-based platform using Ibex Farm (Drummond, 2013). This method was found to be reliable in several previous psycholinguistic studies including those dedicated to L2 processing (e.g., Lago et al, 2019).…”
Section: Methodsmentioning
confidence: 76%
“…2 For Group 3, it was run on a web-based platform using Ibex Farm (Drummond, 2013). This method was found to be reliable in several previous psycholinguistic studies including those dedicated to L2 processing (e.g., Lago et al, 2019).…”
Section: Methodsmentioning
confidence: 76%
“…On the contrary, grammatical sentences are predicted to remain unaffected (but see Sturt, 2018 andJäger et al, 2017 for inhibitory interference in grammatical sentences with longdistance dependencies) given that the verb is not specified for number and the first NP offers a full match. Certain studies on comprehension have confirmed this hypothesis, mostly for number (e.g., Wagers et al, 2009;Lago et al, 2015Lago et al, , 2018Slioussar, 2018).…”
Section: Background Agreement Attraction Accountsmentioning
confidence: 89%
“…Additionally, 104 filler sentences were constructed; half of them were ungrammatical including a variety of violations. The agreement target was in sentence-final position following the previous literature of s-GJTs (e.g., Tanner et al, 2014;Lago et al, 2018;Hammerly et al, 2019) and an adverb (Supplementary Material S5) was also added before the agreement target to increase the processing demands of the task ("John was looking for the recipe for the bread and (he) eventually found it").…”
Section: Materials and Designmentioning
confidence: 99%
“…Let us start with number agreement attraction in comprehension in its reading times reflex. This has been documented in English (Wagers et al, 2009;Tanner et al, 2014;Parker & An, 2018), German (Lago & Felser, 2018), Turkish (Lago et al, 2019;Turk & Logačev, 2021), Spanish (Lago et al, 2015), Armenian (Avetisyan et al, 2020), Arabic (Tucker et al, 2015), French (Franck et al, 2015), and Russian (Slioussar, 2018). These studies represent a substantial amount of evidence in favour of the effect bein robust and present across different languages, which has also been supported by a meta-analysis (Jäger et al, 2017).…”
Section: Introductionmentioning
confidence: 66%